Metagenomic next-generation sequencing assistance in identifying non-tuberculous mycobacterial infections - Shilei Wang; Lihua Xing (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionThe advent of metagenomics next-generation sequencing (mNGS) has garnered attention as a novel method for detecting pathogenic infections, including Non-Tuberculous Mycobacterial (NTM) and tuberculosis (TB).However, the robustness and specificity of mNGS in NTM diagnostics have not been fully explored.MethodsIn this retrospective study, we enrolled 27 patients with NTM genomic sequences via mNGS and conducted a comprehensive clinical evaluation.ResultsPulmonary NTM disease was the most commonly observed presentation, with a subset of patients also presenting with extrapulmonary NTM infections.mNGS analysis identified six distinct NTM species, primarily Mycobacteriumavium complex (MAC), followed by Mycobacterium intracellulare andMycobacterium abscessus. Conventional routine culture methods encountered challenges, resulting in negative results for all available 22 samples. Among the 10 patients who underwent quantitative polymerase chain reaction (qPCR) testing, five tested positive for NTM.DiscussionIt is important to note that further species typing is necessary to determine the specific NTM type, as traditional pathogen detection methods serve as an initial step. In contrast, when supplemented with pathogen data, enables the identification of specific species, facilitating precise treatment decisions. In conclusion, mNGS demonstrates significant potential in aidingthe diagnosis of NTMdisease by rapidly detecting NTM pathogens and guiding treatment strategies. Its enhanced performance, faster turnaround time (TAT), and species identification capabilities make mNGS a promising tool for managing NTM infections.